2021
DOI: 10.3390/biomedicines9101326
|View full text |Cite
|
Sign up to set email alerts
|

Protein-Bound Uremic Toxins Induce Reactive Oxygen Species-Dependent and Inflammasome-Mediated IL-1β Production in Kidney Proximal Tubule Cells

Abstract: Protein bound-uremic toxins (PBUTs) are not efficiently removed by hemodialysis in chronic kidney disease (CKD) patients and their accumulation leads to various co-morbidities via cellular dysfunction, inflammation and oxidative stress. Moreover, it has been shown that increased intrarenal expression of the NLRP3 receptor and IL-1β are associated with reduced kidney function, suggesting a critical role for the NLRP3 inflammasome in CKD progression. Here, we evaluated the effect of PBUTs on inflammasome-mediate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 76 publications
(93 reference statements)
1
24
1
Order By: Relevance
“…Pathogenic mechanisms of oxidative stress in CKD have extensively been reported and discussed [ 100 , 101 , 102 , 103 , 104 , 105 ]. Specific factors, both positive and negative, that influence the overall extent of oxidative stress in human CKD are, for example, related to treatment modality or medication [ 106 , 107 ] and uremic toxin accumulation [ 108 , 109 , 110 ]. The differential expression of antioxidant and mitochondrial enzymes such as superoxide dismutase 1/2 (SOD1/2), thiosulfate sulfurtransferase (rhodanese), or GPx in dependence of CKD stage or severity is well-described [ 111 , 112 , 113 , 114 ].…”
Section: Clinical Data Of Nrf2 Activation In Human Ckdmentioning
confidence: 99%
See 1 more Smart Citation
“…Pathogenic mechanisms of oxidative stress in CKD have extensively been reported and discussed [ 100 , 101 , 102 , 103 , 104 , 105 ]. Specific factors, both positive and negative, that influence the overall extent of oxidative stress in human CKD are, for example, related to treatment modality or medication [ 106 , 107 ] and uremic toxin accumulation [ 108 , 109 , 110 ]. The differential expression of antioxidant and mitochondrial enzymes such as superoxide dismutase 1/2 (SOD1/2), thiosulfate sulfurtransferase (rhodanese), or GPx in dependence of CKD stage or severity is well-described [ 111 , 112 , 113 , 114 ].…”
Section: Clinical Data Of Nrf2 Activation In Human Ckdmentioning
confidence: 99%
“…Indoxyl sulfate , a metabolite of the tryptophan pathway, is one of the very important uremic toxins [ 118 ]. Indoxyl sulfate (43 mg/L) induced the production of ROS in proximal tubule epithelial cells [ 109 ]. In addition, indoxyl sulfate activates the arylhydrocarbon receptor (AhR).…”
Section: Clinical Data Of Nrf2 Activation In Human Ckdmentioning
confidence: 99%
“…The NLRP3 in ammasome is a group of pattern recognition receptors involved in various innate immune responses to both microbial and non-microbial stimuli [23]. Previous research has indicated that the NLRP3 in ammasome is implicated in the regulation of intestinal homeostasis and can be activated by bacterial products such as lipopolysaccharide (LPS) and gutderived uremic toxins like indoxyl sulfate (IS) [24][25][26]. Therefore, it is reasonable to hypothesize that the NLRP3 in ammasome participates in the cross-talk between the microbiota, in ammation, and kidney axis.…”
Section: Introductionmentioning
confidence: 99%
“…In CKD patients, activation of the NF-ĸB pathway due to elevated levels of microbial metabolites such as p-cresol, trimethylamine and indole propionic acid leads to systemic inflammation [ 33 , 34 ] which translates to a high risk of atherosclerosis. The accumulation of uremic metabolites leads to reactive oxygen species (ROS) formation in the kidney epithelial cells by inflammasome-mediated IL-1β production [ 35 ].…”
Section: Introductionmentioning
confidence: 99%